Study on the influence of constructional column on the seismic performance of infilled wall frame structure. (1st January 2023) - Yuan, Shucheng; Lin, Haifeng; Zhu, Zhanyuan; Liang, Wei; Zou, Zuyin; Chen, Wei; Wei, Tao; Cheng, Xuanhao; Guo, Zihong
Abstract: Aiming at the problems of poor construction quality and low efficiency in the construction of cast-in-situ constructional columns, this paper puts forward a kind of fabricated constructional column. Through four full-scale model tests and numerical simulation, the hysteretic energy consumption, stiffness degradation and deformation capacity of infilled wall frames with fabricated constructional columns were studied. The results showed that the specimens with fabricated constructional columns have good in-plane seismic performance. The test phenomenon showed that the crack development mode of masonry infilled wall was changed by the setting of cast-in-situ constructional columns, and its failure was mainly the "X" shaped shear crack. The failure of the infilled wall without any constructional column or with the fabricated constructional column was mainly caused by the horizontal slip cracks. Compared with the cast-in-situ constructional column specimens, the fabricated constructional column specimen has low damage characteristics under the same drift. Finite element simulation can effectively fit the failure and seismic performance of the specimens. This paper can provide references for the application of the new construction technology. Highlights: The in-plane seismic performance of the infilled wall frame structure with a new convenient construction technology of the fabricated constructional column was researched. The interaction between the fabricated constructional column, wall, and frame was analyzed. The mechanism of crack development on infilled walls influenced by a constructional column was summarized. The fabricated constructional column infilled wall with low damage which is more in line with the "strong frame and weak wall" was proved by the experiment.